Relevance of regulatory T cell promotion of donor-specific tolerance in solid organ transplantation - Sagoo, Pervinder; Lombardi, Giovanna; Lechler, Robert I. (Frontiers in Immunology, 2012)
Current clinical strategies to control the alloimmune response after transplantation do not fully prevent induction of the immunological processes which lead to acute and chronic immune-mediated graft rejection, and as such the survival of a solid organ allograft is limited. Experimental research on naturally occurring CD4+CD25highFoxP3+ Regulatory T cells (Tregs) has indicated their potential to establish stable long-term graft acceptance, with the promise of providing a more effective therapy for transplant recipients. Current approaches for clinical use are based on the infusion of freshly isolated or ex vivo polyclonally expanded Tregs into graft recipients with an aim to redress the in vivo balance of T effector cells to Tregs. However mounting evidence suggests that regulation of donor-specific immunity may be central to achieving immunological tolerance. Therefore the next stages in optimising translation of Tregs to organ transplantation will be through the refinement and development of donor alloantigen-specific Treg therapy. The altering kinetics and intensity of alloantigen presentation pathways and alloimmune priming following transplantation may indeed influence the specificity of the Treg required and the timing or frequency at which it needs to be administered. Here we review and discuss the relevance of antigen-specific regulation of alloreactivity by Tregs in experimental and clinical studies of tolerance and explore the concept of delivering an optimal Treg for the induction and maintenance phases of achieving transplantation tolerance.